Love and attraction : an international conference - Cook, Mark, 1942-; Wilson, Glenn D. (Glenn Daniel) (Pergamon Press, 1979)
Love and Attraction is a collection of papers presented at the International Conference on Love and Attraction. This book is organized into 12 parts encompassing 78 chapters that cover various aspects of the subjects, including friendship, intimacy, and sexuality. The introductory parts deal with the psychological aspects of physical attractiveness, non-verbal intimacy, attraction, and friendship. The subsequent parts examine the geographical difference in mate selection, marital relations, and romantic love. These chapters also look into the structural features of personality, behavior, and romantic love. These topics are followed by discussions of exchange theory applications to love and attraction; the social psychology of human sexuality; relationship between sexual behavior and society; and sex therapy. The final parts are devoted to other sex related topics, including sex therapy, erotica, arousal, child sexuality, and pedophilia. This book will prove useful to psychologists, sociologists, psychiatrists, counselors, and other academic and clinical workers.